Update on BS 7974 and its accompanying Published Documents. Issue 2 (20th September 2019) - Spearpoint, Michael; Hopkin, Danny; Wilkinson, Peter; Harrison, Roger
Abstract : This paper presents the historical context of BS 7974 and its accompanying Published Documents. In 2016, it was decided that the BS 7974 suite needed revision, resulting in a new edition being published this year. The paper discusses the application of the standard to fire safety engineering and the role of the Published Documents. A summary of the content of each Published Document is provided along with an overview of the main changes within the updated editions. Finally, the paper briefly discusses the future role of the BS 7974 suite and the application of fire safety principles in light of the recent introduction of prescriptive requirements within building regulations across the UK.